2008
DOI: 10.1093/humrep/dem345
|View full text |Cite
|
Sign up to set email alerts
|

Sperm fluorescence in situ hybridization study of meiotic segregation and an interchromosomal effect in carriers of t(11;18)

Abstract: The incidence of chromosomally unbalanced or aneuploid gametes varies in the individual translocation carriers even if the same chromosomes are included in the translocation. FISH analysis provides information useful for genetic counseling and assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
2
25
0
1
Order By: Relevance
“…These aberrations principally occur by two mechanisms: unbalanced segregation of the chromosomes involved in the translocation during meiosis, and the occurrence of an interchromosomal effects (Godo et al, 2013). The prevalence of abnormal segregation depends on the specific chromosomes involved in the translocation, the localization of breaks, and the frequency of chiasmata (Vozdova et al, 2008). The incidence of chromosomally imbalance or aneuploid gametes may even vary between individual translocation carriers, even if where the same chromosomes are involved in the translocation (Vozdova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These aberrations principally occur by two mechanisms: unbalanced segregation of the chromosomes involved in the translocation during meiosis, and the occurrence of an interchromosomal effects (Godo et al, 2013). The prevalence of abnormal segregation depends on the specific chromosomes involved in the translocation, the localization of breaks, and the frequency of chiasmata (Vozdova et al, 2008). The incidence of chromosomally imbalance or aneuploid gametes may even vary between individual translocation carriers, even if where the same chromosomes are involved in the translocation (Vozdova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The other way is the increase of the aneuploidy frequencies of other chromosomes that are not related to the rearrangement. While sperm count is inversely correlated with the frequency of contact, oogenesis is relatively preserved in the presence of such chromosomal aberrations as seen in number of families with balanced chromosomal structural rearrangements associated with the female fertility [17]. A significant limitation of this case report is the non-availability of karyotype in other family members.…”
Section: Discussionmentioning
confidence: 86%
“…When gametes with an unbalanced translocation are present, they will infrequently fertilize the ovum to produce abnormal zy- gotes. Hence, determining the frequency of unbalanced gametes can help to establish a reproductive prognosis in individual cases and provide a reasonable assessment of the chances of having a normal or balanced embryo (Vozdova et al, 2008). Vozdova et al (2008) reported that the incidence of chromosomally unbalanced or aneuploid gametes varies in individual translocation carriers, even if the same chromosomes are included in the translocation.…”
Section: Discussionmentioning
confidence: 99%